Բարբառային անվանաբայական հարադրությունները Արցախի գրողների ստեղծագործություններում - Մովսիսյան, Ռենա («Դիզակ պլյուս» հրատարակչություն)
Фразовые глаголы являются наилучшими средствами создания художественных образов, выражения яркости и выразительности языка писателя. Писатели Арцаха в своих произведениях использовали диалектные фразовые глаголы, которые стали предметом нашего исследования. Phrasal Verbs are the best ways of creating feature images and expressing the vividness and expressiveness of the writer’s language. The writers of Artsakh widely used in their works dialectal phrasal verbs that were the subject of our research.
Keywords: Բարբառագիտություն